Prevalence of human papillomavirus genotypes in women treated by the Unified Health System in a population from Northeast Brazil - Karol Fireman de Farias; Edilson Leite de Moura; Adriely Ferreira da Silva; Ithallo Sathio Bessoni Tanabe; Eloiza Lopes de Lira Tanabe; Denise Macedo da Silva; Ana Caroline Melo dos Santos; Cristiane Araujo do Nascimento; Tiago Gomes de Andrade; Danyelly Bruneska Gondim Martins; Elaine Virginia Martins de Figueiredo; José Luiz Lima Filho (Universidade Estadual de Alagoas, 2020)
ABSTRACT: The aim of this study was to present the circulating HPV genotypes in a population from northeast Brazil. HPV was detected by nested-Polymerase Chain Reaction (nPCR) method using primers MY09/11 and GP5+/6+. HPV sequencing was performed by the method of Sanger. The HPV 16 was the most frequent (35.7%), followed by HPV 58 (14.3%). In conclusion, we identified, in one population from Northeast Brazil, a low prevalence of HPV 18 present in the vaccine provided by Unified Health System and a high prevalence of HPV 58 which is not present in this vaccine. KEYWORDS: HPV, Oncology and Woman Healthy.